Energy consumption optimization in the smart homes - Shah, Asadullah (2021)
This research presented IOT based smart home energy consumptions using user confirm matrix. The matrix is measuring user comfort using four parameters in it. Temperature, air quality, along with machine learning algorithms to predict a set of parameters for best use of energy as well as obtaining user comfort.